Upaya Pengelolaan Sampah di Pemukiman Kumuh (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2023)
Garbage has become a problem in various areas, especially in slum areas. The purpose of writing this article is to explain waste management efforts in slum settlements. The method for writing this article is literature study. The results of the literature study that has been carried out are found that there are eight efforts that can be made in managing waste in slum settlements, namely, first, conducting regular counseling about PHBS (Clean and Healthy Lifestyle), second, implementing the 3R (Reduce, Reuce, Recycle) program. third, transporting rubbish twice a week, fourth, providing rubbish bins and waste transport equipment in every household, fifth increasing the number of TPS (Temporary Shelters), sixth carrying out a waste bank program, seventh giving rewards to people who care about cleanliness and managing waste, and eight communities collaborate with the government and private sector in managing waste in slum settlements.